Landscape instability at the end of MIS 3 in western Central Europe: evidence from a multi proxy study on a Loess-Palaeosol-Sequence from the eastern Lower Rhine Embayment, Germany - Fischer, Peter; Hambach, Ulrich; Klasen, Nicole; Schulte, Philipp; Zeeden, Christian; Steininger, Florian; Lehmkuhl, Frank; Gerlach, Renate; Radtke, Ulrich (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
The Lower Rhine Embayment hosts important Loess-Palaeosol-Sequences (LPS) within the western European loess belt yielding valuable information on landscape evolution and palaeoclimatic dynamics. The study focusses on the palaeoenvironmental development based on a LPS from the eastern shoulder of the Lower Rhine Embayment (Dusseldorf-Grafenberg). The palaeoenvironmental development within the study area is presented and discussed based on high-resolution grain size analyses, selected environmental magnetic parameters, and geochemical analyses complemented by luminescence age estimates. Differences in grain size distribution (Delta GSD) as well as the U-ratio clearly reflect main stratigraphical units within the LPS. In addition, the centered-log-ratio transformation of Delta GSD (Delta GSD(clr)), which is sensitive to post-depositional grain size variations, traces units of intensified soil formation. Despite no magnetic enhancement can be observed within the Grafenberg LPS, environmental magnetic parameters combined with selected geochemical analyses (Sr/Rb) provide direct information on the modification of silicates and magnetic minerals in the course of pedogenesis and diagenesis. Overall, the Grafenberg LPS contributes to the understanding of environmental conditions within the Lower Rhine Embayment particularly for the late MIS 3 and the transition to MIS 2. The LPS reflects major shifts in the geomorphic system, which are compared to palaeoenvironmental records from different archives and different geographic regions in north-western Europe indicating a direct relation to North Atlantic Climate oscillations during the last glacial period. It is shown that the Hesbaye unconformity (at the MIS 3/2 boundary) is bound to an erosional event, which can be traced over wide areas within the northern European loess belt. (C) 2017 Elsevier Ltd and INQUA. All rights reserved.